Burrowing Nematode Radopholus similis (Cobb, 1893) Thorne, 1949 (Nematoda: Secernentea: Tylenchida: Pratylenchidae: Pratylenchinae) - Nicholas Sekora; William T. Crow (EDIS)
The burrowing nematode is the most economically important nematode parasite of banana in the world. Infection causes toppling disease of banana, yellows disease of pepper and spreading decline of citrus. These diseases are the result of burrowing nematode infection destroying root tissue, leaving plants with little to no support or ability to take up water and translocate nutrients. Because of the damage that it causes to citrus, ornamentals and other agricultural industries, worldwide, burrowing nematode is one of the most regulated nematode plant pests. This 5-page fact sheet was written by Nicholas Sekora and William T. Crow, and published by the UF Department of Entomology and Nematology, October 2012.